Corporate agility and government regulation as drivers of airport performance and airport sustainability: an SEM-based study in Indonesian airports - Fahmi, Faik; Al Musadieq, M.; Damayanti, Cacik Rut; Pangestuti, Edriana (Frontiers in Sustainability, 2025)
IntroductionThis study examines the effect of Corporate Agility and Government Regulation on Airport Performance and Airport Sustainability, with Airport Performance acting as a mediating variable.MethodsThis study utilized Structural Equation Modeling (SEM) to analyze data obtained from an Indonesian airport managed by PT Angkasa Pura Indonesia.ResultsThe result indicate that Responsiveness is the strongest indicator of Corporate Agility (loading = 0.830), followed by Workplace & People, Technology, Quality, Process Planning, and Competency. The Regulator indicator contributes the most to the Government Regulation variable (loading = 0.875), followed by Catalyst and Facilitator. In terms of Airport Sustainability, Environmental factors emerge as the most dominant (loading = 0.884), followed by Social and Economic aspects. Among five tested direct relationships between variables, four are statistically significant. However, one of the two indirect effects from Government Regulation to Airport Sustainability via Airport Performance is not significant. Overall, the structural model explains 57.1% of the variance in the observed phenomena.DiscussionThese findings offer useful insights for airport policymakers and managers to improve sustainability performance through targeted agility initiatives and regulatory alignment. The study contributes to strategic airport management by identifying key levers that drive both operational performance and environmental responsibility.